A simple decision-making approach for information technology solution selection. (19th June 2019) - Zelenkov, Yuri
Information technology (IT) is an indispensable tool for any organisation today, so the choice of adequate IT solutions is a critically important skill. In the literature, many methods for selecting IT solutions have been proposed, but often they use vague criteria that are very difficult to quantify and complex methods to compare alternatives. So, the application of these methods outside the theoretical articles is restricted, since practitioners need simpler approaches. We propose a simple method of the evaluation of alternative IT solutions based on five criteria, namely the cost of ownership, the time for the change, security risks, acceptance by users, and confidence in the supplier's ability to implement the solution. In accordance with the theory of probabilistic mental models, a reference class is proposed for each criterion and variables that can be measured quantitatively are chosen on its base. To simplify the decision-making process, a weighted production model is used for the comparison of alternatives.